2020
DOI: 10.1371/journal.pone.0238721
|View full text |Cite
|
Sign up to set email alerts
|

Examining the day-to-day bidirectional associations between physical activity, sedentary behavior, screen time, and sleep health during school days in adolescents

Abstract: Background Adolescence is a vulnerable period for experiencing poor sleep health. Growing studies have demonstrated lifestyle behaviors including physical activity (PA), screen time (SCT), and sedentary behaviors (SED) as the potential factors associated with sleep health in adolescents; yet, the evidence is inconclusive and the directionality of temporal associations across school days are not well understood. This study examined the day-today bidirectional associations of lifestyle behaviors with sleep healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 61 publications
3
28
0
1
Order By: Relevance
“…This is consistent with recent research carried out on the European adolescent population and reflects the worrying prevalence of poor sleep quality in this age group [78,89]. One of the reasons that can lead to a worse sleep quality as age increases may be the exposure to screens, since the older the subjects, the longer the time of use of electronic devices [70,90]. In addition, the negative influence is higher when close to bedtime, presenting higher levels of sleep latency and difficulties falling asleep [70,90].…”
Section: Sleep Qualitysupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with recent research carried out on the European adolescent population and reflects the worrying prevalence of poor sleep quality in this age group [78,89]. One of the reasons that can lead to a worse sleep quality as age increases may be the exposure to screens, since the older the subjects, the longer the time of use of electronic devices [70,90]. In addition, the negative influence is higher when close to bedtime, presenting higher levels of sleep latency and difficulties falling asleep [70,90].…”
Section: Sleep Qualitysupporting
confidence: 91%
“…A possible explanation for these results can be found in the lower levels of health-related physical fitness and higher levels of body composition of adolescents from Seville [ 58 ], when compared with Reykjavik and Tartu adolescents [ 59 , 68 , 69 ]. It is known that daily physical activity practice (and the consequent increase of the fitness level) is directly related to ease of falling asleep, thus achieving a longer duration [ 70 , 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extra analyses conducted as part of this study confirm that it is the additional (prolonged) sedentary time during non-school hours that is significantly related to a shorter sleep duration, and not the additional (prolonged) sedentary time during school hours (see Additional file 3 ). This is in line with the study of Kim and colleagues [ 21 ] in which more sedentary time during the after-school period, and not during the school period, was associated with a shorter sleep duration the following night among young adolescents. This means that when promoting the reduction and breaking up of sedentary time during the day, there should be a focus on the non-school hours.…”
Section: Discussionsupporting
confidence: 93%
“…Another study in adolescents from the 6th and 8th grade also observed a bidirectional, negative association between sedentary time, screen-time and sleep duration, although the association varied by the specific sedentary and sleep health parameter used and by the time period of a day (e.g. sitting time during school hours vs. after school hours) [ 21 ]. In both studies sedentary time was measured using hip-worn accelerometers.…”
Section: Introductionmentioning
confidence: 99%